2021
DOI: 10.2991/aer.k.211106.069
|View full text |Cite
|
Sign up to set email alerts
|

Development of an Automation System for Nutrient Film Technique Hydroponic Environment

Abstract: Hydroponic is one of the plant cultivation systems known for its high-quality products. The growth of the plant depends on the composition of nutrient solution and the plant environment. Due to its nutrient absorption process, nutrient solution composition continuously varies in the Hydroponics nutrient solution irrigation system. An automation system is necessary to control and monitor the composition of nutrient solutions. This paper presents the development of an automation system for nutrient film techniqu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…Hydroponics technology for highyielding crops can be automated. Plant factories offer far more tightly regulated settings than greenhouses, where the soil is substituted with non-soil components and nutrients are derived from water-rich nutrients [15].…”
Section: Hydroponicsmentioning
confidence: 99%
“…Hydroponics technology for highyielding crops can be automated. Plant factories offer far more tightly regulated settings than greenhouses, where the soil is substituted with non-soil components and nutrients are derived from water-rich nutrients [15].…”
Section: Hydroponicsmentioning
confidence: 99%
“…An automation system for Nutrient Film Technique Hydroponic system was developed to control and monitor the pH level, Electrical conductivity (EC), Dissolved Oxygen (DO), water temperature, water flow rate, and water level of the nutrients solution in the Hydroponics nutrient solution irrigation system suited for a specific plant [14]. Results revealed that the developed system works properly to monitor and control the environment nutrient solution parameters of Hydroponics.…”
Section: Fig 2 Nutrient Film Techniquementioning
confidence: 99%
“…Hydroponics is a farming technique that is based on the cultivation of hydroculture plants [1]. In this technique, plants are grown in a water medium, without soil, and all the required mineral nutrients are supplied through the water.…”
Section: Introductionmentioning
confidence: 99%